Cost Analysis and Economic Evaluation for The Fabrication Activated Carbon Nanomaterials from Durian Seeds Utilizing Ionic Liquids - Andika Purnama Shidiq; Asep Bayu Dani Nandiyanto; Risti Ragadhita; Meli Fiandini (Research and Social Study Institute, 2023)
Waste Agricultural Biomass (WAB) is a challenging problem in this modern era. The purpose of this study was to evaluate the economic feasibility of manufacturing carbon nanomaterials from durian waste biomass using ionic liquids. Several economic evaluation parameters are analyzed to inform the production potential of valuable materials from Biomass. The results showed that the production of carbon nanoparticles from biomass is quite prospective. Technical analysis for converting 250 kg of waste durian seeds shows the total cost of the equipment purchased was USD 12,086. Adding the Lang Factor, the total investment cost should be less than USD 53,661. This value is relatively economical (ie the project requires less investment funds) to reduce 75 tons per year or 100 tons per 20 project years. Compared to the total amount of degraded durian seed waste, the value is only around 18 USD per ton. Indeed, it is inexpensive to access a problem solver in degrading a ton of durian seed waste. To ensure project feasibility, projects are assessed from ideal to worst conditions in production, including labor, sales, raw materials, utilities, and external conditions (ie, taxes and subsidiaries).